Electron diffraction and high resolution transmission electron microscopy in the characterization of calcium phosphate precipitation from aqueous solutions under biomineralization conditions - Suvorova E. I.; Buffat P. A. (European Cells & Materials, 2001)
Calcium phosphate precipitation obtained from aqueous solutions at room and body temperature and pH 5.5-7.5 were investigated by high-resolution transmission electron microscopy (HRTEM), transmission electron diffraction, scanning electron microscopy (SEM) and X-ray diffraction (XRD). Supersaturated solutions of calcium phosphates were prepared by different methods of mixing of the stock solutions: diffusion-controlled mixing in space, convection-controlled mixing on earth and forced mixing on earth and with typical physiological parameters (pH and temperature). Concentrations of the stock solutions, rate of solution mixing and duration of precipitation influence very strongly the chemical composition of the precipitation, the phase composition of individual crystals, their sizes, morphology and structure. Microdiffraction and HRTEM techniques showed an incontestable advantage on other techniques like SEM and XRD in the investigation of small particles and mixtures of calcium phosphates (hydroxyapatite and octacalcium phosphate) with different proportions.